Event-Driven Architecture in Retail: Real-Time Inventory Synchronization for Omnichannel Retail - Jose, Nidhin (International Journal of Computing and Engineering, 2025)
Event-Driven Architecture (EDA) offers a transformative solution for real-time inventory synchronization across omnichannel retail environments, addressing critical challenges in maintaining consistent data across physical stores, e-commerce platforms, mobile applications, and social media marketplaces. This comprehensive article examines how EDA fundamentally changes retail inventory management through event-based processing of inventory changes, enabling instantaneous updates across all sales channels. The paradigm shift from traditional batch processing to event-driven systems delivers significant improvements in data consistency, system performance, and business outcomes. Technical implementations leveraging event streaming platforms, microservices architecture, and advanced patterns like Event Sourcing and CQRS provide the foundation for robust inventory management. Though implementation presents challenges in data consistency, system latency, and legacy integration, established patterns and strategies effectively address these concerns. The business value of EDA extends throughout retail operations, enhancing customer experience through accurate inventory information, optimizing supply chain operations through real-time decision-making, and enabling sophisticated analytics capabilities that drive competitive advantage. As retail continues evolving toward increasingly integrated experiences, EDA emerges as a foundational architecture enabling omnichannel excellence.